Pembakaran Sampah Dengan Menggunakan Bahan Plate Berupa Drum Atau Besi Plate (Incenerator) di Pulau Lae-Lae - Musa, Andi Ernie Zaenab; Rachman, Abdul Nasir; Abbas, Abbas (STIE Amkop Makassar, Indonesia, 2023)
The purpose of community service is to provide solutions to the waste management problems faced by the people on the island. Through community service, it is expected to be able to provide education and training to the public in environmentally friendly waste management and to provide an alternative for effective and safe waste handling through the use of incinerators. With this urgency, incineration of waste using plate material in the form of drums or iron plates (incinerator) can be an effective alternative in overcoming the problem of waste handling and minimizing the negative impact on the environment and public health.